Nutrition and Physical Activity in Older Adults with CKD patients: Two Sides of the Same Coin - Claudia D'Alessandro; Domenico Giannese; Maria Rosaria Ruisi; Nicola Pellegrino; Ersilia Lucenteforte; Vincenzo Panichi; Adamasco Cupisti (Karger Publishers, 2024)
Introduction. Nutrition and physical activity are two major issues in the management of CKD patients who are often older, have comorbidities and are prone to malnutrition and physical inactivity, conditions that cause loss of quality of life and increase the risk of death. We performed a multidimensional assessment of nutritional status and of physical performance and activity in CKD patients on conservative therapy in order to assess the prevalence of sedentary behaviour and its relationship with body composition. Methods. 115 consecutive stable CKD patients aged 45-80 years were included in the study. They had no major skeletal, muscular or neurological disabilities. All patients underwent a multidimensional assessment of body composition, physical activity and exercise capacity. Results. Sedentary patients, as defined by mean daily METs < 1.5 were older and differed from non-sedentary patients in terms of body composition, exercise capacity and nutrient intake, even after adjusting for age. Average daily METs were positively associated with lean body mass, muscle strength, 6-MWT performance, but negatively associated with fat body mass, body mass index and waist circumference. In addition, a sedentary lifestyle may have negative effects on free fat mass, muscle strength and exercise capacity, and may increase fat body mass. Conversely, s decrease in muscle mass and/or an increase in fat mass may lead to a decrease in physical activity and exercise capacity. Conclusion. There is a clear association and potential interrelationship between nutritional aspects and exercise capacity in older adults with CKD: they are really the two sides of the same coin.